An Analysis of Children’s Visual Artworks Through Free Drawing in Children Aged 5–7 Years - Prayitno, Prayitno; Harun, Harun; Syamsudin, Amir; Zubaedah, Siti (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Children aged 5–7 years are in the preoperational stage of cognitive development. The problem that occurs in children of this age is that their ability to express their imagination through drawings is still limited. Previous research has not examined how visual expression emerges in early childhood drawings, particularly regarding drawing stages, object shapes, drawing duration, and sources of inspiration. This study aims to analyze the visual expression of drawings by children aged 5–7 years, focusing on drawing stages, object shapes, drawing duration, and sources of inspiration. This study used a descriptive qualitative method. The subjects were 70 kindergarten children in the Special Region of Yogyakarta. Data was collected through interviews, observation, and documentation, then analyzed using reduction, presentation, and conclusion-drawing techniques. The results showed that children's drawing process involves imagination, creativity, and storytelling. The most frequently drawn object was a butterfly, with the longest drawing duration being between 10–15 minutes. Most of the drawings were inspired by children's visual experiences. This study found that 61 children drew based on objects they imagined, while 9 children experienced difficulty expressing ideas visually. This research contributes to early childhood education by stimulating visual expression as a foundation for creativity in kindergarten learning. However, this study was limited to one region and a limited number of subjects, so it does not fully represent the cultural diversity of children. Future research can be conducted on a broader and more diverse range of subjects and children's drawings. Further research may also help children who have difficulty with visual expression.